Compare of Executive Function in Bipolar I Disorder and Schizophrenia - Mohammad Reza khodaei-Ardakani; Mohammad Kamran-Derakhshan; Omid Rezaei; Behrouz Dolatshahi; Arash Mirab-Zadeh (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: There is evidence for differential executive function in Bipolar I Disorder (BID) and schizophrenia that may tend different cognitive deficits and abnormalities. The objective of this sudsy was to compare the executive function of BID and schizophrenic patients. Materials & Methods: We studied 50 patients with BID, and 50 with schizophrenia participants in outpatients' clinic of Rouzbeh hospital. All participants completed the Wisconsin Card Sorting Test (WCST) the Persian version. The participants were mach in three basic variables which had most contributions in cognitive conditions in patients. They were Age, educational status and period of illness. Results: The two patient groups had compared performance on the WCST in compared with general population (P<0/05). In the WCST, schizophrenic patients showed impairment executive function than BID patients (P<0/05). Conclusion: findings indicated that schizophrenic patients had more dysfunctions executive function than the Bipolar disorder I patients. Although, both disorders may show impairment in executive function, but the dysfunction in schizophrenia greater than Bipolar I Disorder patients.